Communication ethics in distribution of information through Youtube social media (Case of teacher sexual harassment on Santriwati) - Purwatiningsih, Sri Desti (Technium Social Sciences Journal, 2022)
In social life, YouTube as a social media is often used to spread messages and information quickly on a large scale to its users at a relatively low cost. The purpose of this study is to identify and describe communication ethics in the use of youtube social media as a means of information media for youtube users through a geographic method approach, which is a method used to understand the culture of social media users as a safe space for youtube social media users in sharing information. Netnography is a method for investigating social media users’ behavior (culture) or habits. This research is only focused on communication ethics in the use of YouTube social media as a medium for disseminating and fulfilling information for the community by raising a case about the harassment and rape of a religious teacher as well as the owner of a boarding school to his students to give birth to a baby. The problems studied were cases of harassment and rape against female students that occurred in several Islamic boarding schools that were carried out by the teacher/ustad himself.